Description Of the Test Bench and The Method of Measuring the Main Characteristics of Thin Plate Knives - Urinov Nasillo Fayzilloevich; Amonov Mahmud Idris ugli; Sokhibov Ibodullo Adizmurodovich; Sayliev Ismat Ismatovich (Zien Journals, 2022)
The article covers the technological reliability of thin lamellar knives in terms of dimensional accuracy and shape of the cut blanks, the main reasons causing the deviation of the cutting edge from the cutting plane have been identified, structural diagram of the lateral deviation of the lamellar knife and experimental setup have been developed
Keywords: static stability; diagram of technological forces; thin lamellar knife; cutting edge